Saving in India - National Council of Applied Economic Research (New Delhi, 1961)
The dependence of economic development upon an adequate level and composition of saving hardly requires elaboration. Unfortunately, econo mic planning in India has had to cope with lack of knowledge on how much is saved, who does the saving, what form the saving takes and the motivating forces for such saving in our economy. The National Council of Applied Economic Research addressed itself to filling this major gap in our economic intelligence and providing comprehensive data on savings for different sectors in the Indian economy as early as 1958. The Council adopted two different prongs to the study: a survey approach which would provide distributional and motivational data for the Individuals' sector which forms, of course, the single most important sector in the economy and an aggregate approach which would provide the most reliable estimates of saving for the economy as a whole. The National Council conducted a pilot survey of Urban Saving in Delhi in 1959 and developed appropriate methods and techniques for a large scale survey. The all-India Urban Saving Survey was started in April 1960 and a preliminary report on the findings is expected very soon. A pilot rural survey is already in the field with a view to appraising the magnitude and forms of saving that originate in the rural sector and an all-India survey will be undertaken.
Keywords: Saving and investment